Understanding relations between scripts : the Aegean writing systems - Steele, Philippa M., 1983- (Oxbow Books, 2017)
Examines the writing systems of the ancient Aegan and Cyprus in the second and first millennia B.C., principally Cretan hieroglyphic, Linear A, Linear B and Cypro-Minoan. These scripts, of which some are deciphered and others are not, are known to be related to each other. However, the details of their relationships with each other have remained poorly understood and this is the first volume dedicated solely to exploring this issue. Nine expert contributors aim to reach a better appreciation of relationships between the writing systems than has been possible in previous research, through an interdisciplinary dialogue that takes account both of features of the writing systems and of the contextaul factors affecting the ways in whcih writing systems and of the contectual factors affecting the ways in which writing was used and passed on. Each individual contribution furthers this aim by presenting the latest research on the Aegean scripts, demonstrating the great advances in our understanding of sscript relations that are possible through such detailed and innovative studies - cover.